2022
DOI: 10.1007/s11123-022-00628-1
|View full text |Cite
|
Sign up to set email alerts
|

The choice of efficiency benchmarking metric in evaluating firm productivity and viability

Abstract: The Debreu–Farrell measure of technical efficiency is widely used to benchmark firm performance. A limitation of this measure is that it is orientation restricted and evaluates the performance of a decision-making unit in an explicit direction relative to the best-practice frontier and not the most productive point on the frontier. Therefore, the measure does not provide policy insight on how to direct decision-making units to achieve the best possible productivity level. Taking a departure from conventional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
1
1
0
Order By: Relevance
“…This result aligns with the findings of West et al. (2022), where the authors observed that the bias correction factors were approximated to zero.…”
Section: Resultssupporting
confidence: 92%
“…This result aligns with the findings of West et al. (2022), where the authors observed that the bias correction factors were approximated to zero.…”
Section: Resultssupporting
confidence: 92%
“…Of the surveyed farm businesses, 29 are in the medium rainfall zone and 25 in the low rainfall zone. In prior studies in the region, farm businesses in the low rainfall region have been found to have lower productive performance and greater reliance on debt in their capital structures (West et al, 2021(West et al, , 2022. Primary operator age is included to examine whether management experience is significant to efficiency; older primary farm business operators are hypothesised to have greater experience and use resources more efficiently.…”
Section: St U Dy R Egion a N D Datamentioning
confidence: 99%
“…A higher ratio of off‐farm income to aggregate receipts is expected to increase partial inefficiency; this is because farm operators must direct more time and knowledge away from farming activities to generate off‐farm income (Mishra & Sandretto, 2002; Sabasi et al., 2019; Yee et al., 2004). Farm business size as measured by total revenue is considered as a determinant of partial inefficiency; several prior studies in developed countries have found that larger farm businesses exhibit higher productive performance (Key, 2019; Key et al., 2008; Mugera & Langemeier, 2011; Rada & Fuglie, 2019; Sheng et al., 2014; Sheng & Chancellor, 2019; West et al., 2022). To investigate the impact of rainfall zone on partial inefficiency, a dummy variable is constructed based on the Western Australian Department of Agriculture and Food's rainfall zone classification.…”
Section: Study Region and Datamentioning
confidence: 99%
“…Hence, benchmarking results are used to identify, quantify and prioritize the improvement opportunities offering the greatest potential returns while highlighting the areas at risk due to underspending. These results provide a factual basis and context for creating a business plan to drive change (West et al, 2022;Szydełko, 2021). Benchmarking may be a one-off event but is often treated as a continuous process in which companies continually seek to challenge their practices.…”
Section: Benchmarkingmentioning
confidence: 99%